Motivated Risk Assessments - Marco Islam (Lund University, School of Economics and Management, Department of Economics, 2021)
How do people assess risks associated with a hedonic but dangerous activity? I conduct a longitudinal field experiment (N=434) exploiting the conditions of the COVID-19 pandemic to investigate whether monetary incentives induce people to motivate their risk assessments. Each participant receives a café voucher with a random value: treated participants receive a 10EUR voucher, and the control group a 1.50EUR voucher. The results show that subjects who receive a high incentive not only visit cafés more often but also reduce their risk assessment relative to subjects with a low incentive. Importantly, the assessment updating happens in anticipation of the visit, suggesting that it justifies a risky activity. This finding is inconsistent with the standard notion of Bayesian updating but consistent with motivated reasoning. It is robust to different risk measures (incentivized and non-incentivized) and does not lend support for alternative explanations, such as visits at less busy times or additional information acquisition. The data further suggests that the formation of motivated risk assessments is supported by selective recall of previous assessments. Treated subjects systematically underestimate former assessments relative to subjects of the control group.
Keywords: C93; D03; D91; 330; Risk Assessment; Motivated Reasoning; Self-Deception; Field Experiment